Microscopic and molecular detection of Giardia spp. in fecal samples among shelter dog population in Selangor - Magdalene, Stephanie (2017)
Giardia spp. is a protozoan that can be found in feces of human and animals and is considered to have zoonotic potential. In vertebrates, including mammals, birds, reptiles and fishes, clinical signs like diarrhea, vomiting, weight loss and lethargy are frequently observed while in humans, various clinical manifestations have been reported ranging from asymptomatic to acute, intermittent or chronic non-bloody diarrhea. This study aimed to determine the occurrence of Giardia spp. in fecal samples of dogs from various canine shelters in Selangor by using microscopic and polymerase chain reaction (PCR) detection methods. Secondly, the occurrence of Giardia spp. was investigated for its association with occurrence of diarrhea. This project was approved by the UPM animal ethics committee and consent received from the five shelters. A total of 130 dogs were randomly selected based on convenience sampling. Fecal swabs were obtained and rolled onto glass slides, air-dried and stained with both Giemsa and Ziehl-Neelson and microscopically examined. Seventy fecal samples were sufficient for nested-PCR assay where primers specific for Giardia were used, and subsequent gel electrophoresis to determine the specific bands corresponding to the PCR product band size. Statistical analysis was done using SPSS where P-value<0.05 was considered significant. Giardia spp. was detected from four dogs out of 130 dogs (3.1%) on microscopic evaluation which was confirmed on PCR detection. Other parasites detected by microscopic examination include Cryptosporidium and coccidia. A total of 17.1% (n=12/70) of the samples were positive for Giardia spp. by nested-PCR detection method. There was four times higher positive detection of Giardia spp. in dogs with diarrhea and it was statistically significant through Pearson's chi-squared analysis (P value=0.044). In conclusion, this study reports for the first time molecular detection of Giardia spp. in 17.1% of shelter dogs in Malaysia using molecular detection method. It is recommended that all shelter dogs should be periodically dewormed to prevent transmission of Giardia spp. among the shelter animals within the same enclosures and avoid potential zoonotic transmission to care takers of the shelter. Phylogenetic characterization of Giardia spp. in dogs in Malaysia merit further studies.